Limit points of Aα-matrices of graphs - Oliveira, Elismar R.; Trevisan, Vilmar (Linear algebra and its applications, 2026)
We study limit points of the spectral radii of Aα-matrices of graphs. Adapting a method used by J. B. Shearer in 1989, we prove a density property of Aα-limit points of caterpillars for α close to zero. Precisely, we show that for α∈[0,12) there exists a positive number τ2(α)>2 such that any value λ>τ2(α) is an Aα-limit point. We also determine other intervals whose numbers are all Aα-limit points.